A Case of Recurrent Coronary Subclavian Steal Syndrome - Vasigh, Mostafa (Cureus, 2020)
Coronary subclavian steal syndrome (CSSS) is one of the rare complications of coronary artery bypass graft surgery (CABG). This phenomenon is a potential complication after left internal mammary artery (LIMA) to left anterior descending artery (LAD) CABG. A proximal stenosis of the left subclavian artery (SA) could cause retrograde flow from LIMA to left SA, which characterizes the mechanism of CSSS. We describe a unique case of recurrent CSSS in a 64-year-old female who presented with one month of exertional dyspnea and acute onset chest pain. She had an extensive coronary artery disease history with CABG 15 years prior to presentation and CSSS treated with left SA stent placement nine years later. She also underwent percutaneous intervention with stents placed in the saphenous vein graft. Although electrocardiogram, cardiac enzymes, and stress test did not show any evidence of acute ischemic changes, perfusion scan detected large areas of partially reversible ischemia. Cardiac catheterization was performed, which showed in-stent restenosis of the left SA and retrograde flow from the LIMA to the left SA indicative of recurrence of CSSS. Left SA arteriogram confirmed in-stent restenosis of the left SA, which was treated with balloon angioplasty and stent placement.